IMPLEMENTASI MODEL (PBL) BERBANTUAN APLIKASI BUDAYA INDONESIA UNTUK MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR PANCASILA PESERTA DIDIK KELAS IV SD NEGERI SUMOBITO 1 - Saifuddhin, Hadi; Suprayitno, Suprayitno; Zuliana, Deni (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
The type of Classroom Action Research (PTK) used in this experiment. The focus is on improving Pancasila activities and learning outcomes by implementing the Problem-Based Learning model, assisted by Indonesian culture application media for class IV students at Sumobito I State Elementary School. As a result, aspects of activities and teaching and learning outcomes in each cycle show a significant increase. Where the first cycle of teacher activities obtained a percentage of 75% and the second cycle obtained a percentage of 90%. Likewise with student activities, in cycle I the percentage gain was 76.45% and cycle II 84.55% which shows an increase. For complete learning outcomes in cycle I, the percentage was 70.5% and the increase in cycle II was 88.23%. Based on these data, it was concluded that applying the Problem-Based Learning model assisted by Indonesian cultural application media for class IV students at SDN Sumobito I was able to improve the learning process for Pancasila subjects, especially aspects of teacher activities and student learning outcomes.